Impact of Prepectoral vs. Subpectoral Tissue Expander Placement on Post-mastectomy Radiation Therapy Delivery: A Retrospective Cohort Study - Libby R. Copeland-Halperin, MD; Yulia Lyatskaya, PhD; Jennifer R. Bellon, MD; Tanujit Dey, PhD; Matthew J. Carty, MD; Thanh Barbie, MD; Jessica Erdmann-Sager, MD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Implant-based reconstruction is the most common method of postmastectomy reconstruction. Many patients require postmastectomy radiation (PMRT). Tissue expanders (TEs), typically inserted as a first stage, have historically been placed subpectorally. More recently, prepectoral reconstruction has gained popularity, but its impact on PMRT is unknown. Prior studies focus on complication rates and aesthetic outcomes. This study examines whether there is a difference in radiation dosimetry among patients undergoing prepectoral versus subpectoral TE reconstruction. Methods:. Electronic medical records and radiation plans of 50 patients (25 prepectoral, 25 subpectoral) who underwent mastectomy with immediate TE reconstruction at our institution or affiliate site were reviewed. Pectoralis major muscle and chest wall structures were contoured and mean percentage volumes of these structures receiving less than 95%, 100%, and more than 105% target radiation dose were calculated, as were heart and ipsilateral lung doses. Welch two sample t test, Fisher exact test, and Pearson chi-squared tests were performed. Results:. The groups had comparable patient and tumor characteristics and underwent similar ablative and reconstructive procedures and radiation dosimetry. Subpectoral patients had larger mean areas receiving less than 95% target dose (“cold spots”); prepectoral patients had larger mean areas receiving greater than 105% (“hot spots”) and 100% target doses. There were no differences in chest wall, heart, and lung doses. Conclusions:. Our results demonstrate an increased mean percentage area of pectoralis cold spots with subpectoral reconstruction and increased area of hot spots and 100% dose delivery to the pectoralis in prepectoral patients. Larger studies should analyze long-term effects of prepectoral reconstruction on radiation dosing and recurrence rates.